PEMBEBASAN NARAPIDANA DALAM PRESPEKTIF KONSEP ASIMILASI PANDEMI COVID-19 - Rizqi Mely Trimiyati (Journal Publicuho, 2021)
The policy of the Minister of Law and Human Rights of the Republic of Indonesia Number 10 of 2020 regarding the release and release of prisoners through the process of assimilation and integration in the response to Covid-19 caused many pros and cons. There are some groups who judge that the decision is the right step to respect the law and the Criminal Justice System. The research method used in this study is a normative juridical approach, namely through the analysis of a legal problem according to the provisions of the applicable laws and regulations. The type of legal material used is primary law, namely related legislation and secondary legal materials in the form of literature that the author reads such as scientific articles and books. The deepening of this research uses descriptive analytical method which has the aim of being able to describe precisely where in this study the object of research is the release of prisoners in the perspective of the concept of assimilation. The purpose of this research is to find out and understand how the release of prisoners from the perspective of the concept of assimilation is viewed from the point of view of punishment. Based on the results of the study, it showed that the assimilation policy given to prisoners during the Covid-19 pandemic was in accordance with the concept of assimilation, namely by fulfilling the requirements and conditions as stipulated in the legislation. The Class IIB Bantul State Detention Center continues to monitor inmates who are undergoing a virtual assimilation program and continues to coordinate with law enforcement officials including the National Police, Attorney General's Office, Courts, and community leaders around the prisoners' residences.